If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 2m + 2 + 6m Reorder the terms: 2 = 2 + 2m + 6m Combine like terms: 2m + 6m = 8m 2 = 2 + 8m Add '-2' to each side of the equation. 2 + -2 = 2 + -2 + 8m Combine like terms: 2 + -2 = 0 0 = 2 + -2 + 8m Combine like terms: 2 + -2 = 0 0 = 0 + 8m 0 = 8m Solving 0 = 8m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8m' to each side of the equation. 0 + -8m = 8m + -8m Remove the zero: -8m = 8m + -8m Combine like terms: 8m + -8m = 0 -8m = 0 Divide each side by '-8'. m = 0 Simplifying m = 0
| (q*q*q)-6(q*q)-21600=0 | | 12/3x5-16 | | 10-x/4x | | 6(2x+2)+15= | | -2/-1 | | 0=x^4-6x^3-x^2+20x | | 2.6-5.1=6.6 | | 3x/4-1/3(3x-6)=5/2(6-x/2) | | 6(2x^2-9x-18)=0 | | 8x/3-2x-6 | | 11x^3-x+9=x^3+45x^2+x | | 683+2x=53 | | 18-(2m+5)=4+2m-15 | | 6(4x+15)+13x-12= | | 31/5+x=6 | | a=-2(1.4c)+4c | | 18080-5x=8 | | -x-6y=-5 | | 21/5+x=6 | | 4(x-80)+10=-10 | | 4(5x+6)+7(12-x)= | | 3+z=-19 | | -1+a=0.5 | | 69-(7x+4)=7(x+5)+x | | [-x]=-1 | | 9x-18=40+3x | | 7-12x/4 | | 2x+3x+9=8 | | 6x^2+28x+26=0 | | 10=-12-e | | (7x+13)+(7x-2)= | | -2(y-3)=y+4s |